Strategy for Improving the Economy of Seaweed Farmers Through Strengthening Infrastructure and Technology in Tekolabbua Urban Village - Musmahendra Musmahendra; Surianto Surianto (Eastasouth Institute, 2026)
This study aims to analyze sustainable development planning strategies based on the local potential of seaweed products to increase the income of local communities in Tekolabbua Urban Village, Pangkajene District, Pangkep Regency. The study uses a qualitative descriptive approach with data collection techniques through Focus Group Discussions, interviews, field observations, and documentation. Research informants include seaweed cultivator groups, women's groups, community leaders, group leaders, and relevant stakeholders. The results show that Tekolabbua has strong ecological and social potential for seaweed development, particularly due to the availability of ponds, community cultivation experience, and the presence of local groups. However, the development strategy has not been optimal because cultivation remains traditional, post-harvest processing is limited, economic institutions are weak, market access depends on middlemen, and community income fluctuates due to prices and environmental conditions. The findings emphasize the need for an integrated strategy that includes improving human resource capacity, strengthening cooperatives or local economic institutions, product diversification, market partnerships, provision of post-harvest infrastructure, and environmental risk mitigation. The novelty of this study lies in integrating upstream-downstream dimensions, institutions, added value, women's empowerment, and environmental sustainability into a single framework for local development planning based on seaweed. Practically, the results provide a basis for local governments and communities to design participatory, adaptive, and sustainable seaweed development programs in local coastal areas.